Surgical Specifics of Lower Limb Superficial Thrombophlebitis Combined with Undifferentiated Connective Tissue Disease - M. V. Timerbulatov; T. M. Murasov; A. M. Murasov (Креативная хирургия и онкология, 2022)
Background. Superficial thrombophlebitis of lower extremities is among the most frequent acute vascular pathologies. Concomitant undifferentiated connective tissue dysplasia exerts specific changes in its clinical course.Aim: A study of the specific dynamics of acute lower limb superficial thrombophlebitis (ST) and its surgical treatment in patients with undifferentiated connective tissue dysplasia (UCTD).Materials and methods. The case histories, surgery reports and follow-up examinations of patients treated at the Vascular Surgery Unit during 2012–2020 were analysed. A total of 86 patients had signs of UCTD and underwent classical crossectomy of the great saphenous vein (Troyanov operation).Results and discussion. Duplex ultrasound of lower limb veins in 34 (39.53 %) patients revealed a discrepancy between the upper localisation of thrombotic masses in the great saphenous lumen and the external boundary registered for clinical manifestations, hyperaemia and tissue thickening. In 69 (80.23 %) patients, four or more phenotypic UCTD markers were exposed. In 74 (86.05 %) cases, a classical Babcock phlebectomy was performed as a next stage within one year after an acute thrombophlebitis attack had subsided. Of 12 (13.95 %) patients not having had a second-stage phlebectomy within one year: 4 people had UCTD signs — they refused surgery due to absent significant complaints or marked saphenous reflux; 3 had a deep vein thrombosis episode; 5 had no saphenous reflux of lower extremities in ultrasound examination.Conclusion. The registration of phenotypic signs of undifferentiated connective tissue dysplasia is recommended in choosing a surgical tactic to treat acute ascending thrombophlebitis of lower limb saphenous veins.